Investigating the meaning of Al-'ifk and Al-kadhib (Lie) and their English Translation by Abdullah Yusuf Ali - Abdul-Qader Khaleel Mohammed Abdul-Ghafour; Yasser Alrefaee; Sameer Boset; Morshed S. Al-Jaro (Hasanuddin University, 2019)
This study investigates the meaning of the Qur'ānic near-synonyms الإفك al-'ifk and الكذب al-kadhib (lie) and their English translation. It aims to identify the contextual meaning of these Qur'ānic near-synonyms based on the exegeses of the Holy Qur'ān. Then, it explains the nuances that exist between these two lexical items in terms of denotative meaning. This study also examines how the semantic differences between these Qur'ānic near-synonyms are reflected in the English translation of the Holy Qur'ān by Ali (2006). This study adopts the RC-S approach by Murphy (2003) as a theoretical framework for data analysis. It also employs the qualitative approach to collect and analyze the data of the study. The exegeses of the Holy Qur'ān are consulted to identify the semantic differences between the Qur'ānic near-synonyms. The findings reveal that there exist some differences in meaning between these Qur'ānic near-synonyms in terms of denotative meaning and that the semantic differences between these Qur'ānic near-synonyms are not reflected in Ali's English translation of the Holy Qur'ān. The study provides recommendations for readers and translators especially the translators of the Holy Qur'ān.